The Effect of Implementing Visual Learning Method Using Picture Media to Improve Poetry Writing Learning Competencies - Ndruru, Dafid Timotius; Kartolo, Rahmat; Sutikno, Sutikno (PT Inovasi Pratama Internasional, 2025)
This study aims to examine the differences and effectiveness of using nature-themed image media in poetry writing lessons among eighth-grade students at SMP Negeri 2 Alasa, North Nias Regency, during the 2024-2025 academic year. The subjects of this study were 28 students. The experimental method with an experimental research design was applied. Data were collected through poetry writing tests and using analyzed statistical tests. The analysis results indicate a significant difference in poetry writing performance between students taught using nature-themed image media and those taught without it. The average score of the experimental group was higher than that of the control group, demonstrating that using nature-themed image media effectively improves students' poetry writing skills. Furthermore, this media aids students in developing their imagination and a deeper understanding of the given theme, leading to more creative and expressive writing outcomes. Based on these findings, it is recommended that teachers consider using nature-themed image media in poetry writing lessons to enhance student interest and skills. Visual media relevant to the lesson theme can serve as inspiration for students, improving the quality of their written work.